Pengembangan model pembelajaran scientific untuk meningkatkan ketuntasan belajar bahasa Inggris tema “recount text” deskriptif lisan dan tulis, pendek dan sederhana, tentang orang, binatang, dan benda di kelas 8 MTs Negeri Sooko Mojokerto - Rodhi, Mohammad (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
The process of scientific work, promoting inductive reasoning rather than deductive reasoning. Inductive reasoning sees a specific phenomenon or situation to then draw an overall conclusion. Especially in the learning of Writing (writing), some things are perceived as a constraint of them is that this learning requires careful planning so that students can achieve basic competence indicator. The purpose of this research development is: 1) Describe the learning tools developed in the model of scientific learning to improve the completeness of learning English the theme of "recount text" descriptive oral and written, short and simple, about people, animals and objects in 8th grade MTs Negeri Sooko Mojokerto 2) Analyze the scientific learning model able to improve the completeness of learning English theme "recount text" descriptive oral and written, short and simple, about people, animals, and objects in grade 8 MTs Negeri Sooko Mojokerto. Selection and use of scientific learning model properly can streamline and streamline the implementation of learning. For that purpose the scientific learning model is absolutely necessary. 1) The product of scientific learning model to improve learning comprehension of English "recount text" has been refined based on analysis of trial data. Based on the steps that have been implemented can be concluded as follows. 1). Learning tool developed is RPP / Scenario Learning is feasible to be used for the test because the score of each component which is an indicator for English "recount text" with scientific learning model none less than 3.0 2) Analyze scientific learning model capable To improve the English learning completeness of the theme of "recount text" descriptive oral and written, short and simple, about people, animals, and objects in grade 8 MTs Negeri Sooko Mojokerto obtained average student choice is 3.63, it is categorized Enough with standard intersection 0.25